Pravna ureditev poskusov na živalih in pogoji za pridobitev dovoljenja - Perše, Martina (Medicinski razgledi, 2006)
In Slovenija, the use of experimental animals in education and for experimental and other scientific purposes is regulated by the Animal Protection Act and other subsidiary legal acts, in which the legal provisions of the European Union have been adopted. In the article, the authors explain in brief the conditions for the acquisition of the permit for carrying out animal experiments in Slovenia.
Keywords: Animal Rights; Žival, pravice; Žival, zaščita; Animal Welfare; Animals, Laboratory; Živali laboratorijske; poskusi na živalih; pravna ureditev